Teaching And Learning Writing Using Teacher’s Written Feedback And Conference - Iisrohli Irawati (UIN Salatiga, 2012)
The objective of this study is to find out whether there is a significant difference in terms of writing skills improvements between the 8th grade students of SMP N 1 Prambanan Sleman who are given teacher’s written feedback and conference and those who are not in the academic year of 2011/2012. This study involved 71 students from two groups, Class VIII B (35 students) as the experimental group and Class VIII A (36 students) as the control group. The experimental group was given teacher’s written feedback and conference in the writing learning process, whereas the control group was given peer’s feedback. The data were obtained by using two essay writing tests. They were administered to the two groups as the pre-test and post-test. The pre-test was given to both groups before the treatment was given and the post-test was given after the treatment finished. The data of the pre-test and post-test of both groups were analyzed by means of descriptive and inferential statistics. After the data were tested and found to be homogeneous and normal, the hypothesis was tested using the analysis of covariance (ANCOVA). The results show that there is a significant difference in the writing ability between the students who are given teacher’s written feedback and conference and those who were not. It can be seen in the result of the hypothesis testing using ANCOVA. The significant value of 0.001 is less than the significance level of 0.05 (0.001 0.05), which means that the data of this study are considered to have a significant difference. Therefore, the hypothesis of this study is accepted. It means that the technique of giving teacher’s written feedback and conference significantly improves the students’ writing ability in the English teaching and learning process in SMP N 1 Prambanan Sleman. Keywords : Teaching and Learning Writing; Teacher’s Feedback and Conference; Experimental Research